Psychological Dynamics of a Male Child Patient with Paranoid Schizophrenia Symptoms - Margaretha Oktaviana Suryaningrum; Fitrania Maghfiroh (International Conference on Psychology and Education (ICPE), 2024)
Paranoid schizophrenia is one of the variants of schizophrenia characterized by the dominance of paranoid symptoms, such as delusions often related to suspicion or threats from others, and it may also be accompanied by auditory hallucinations, which involve hearing voices that are not present. Paranoid schizophrenia, according to PPDGJ, is a subtype of schizophrenia marked by the presence of dominant delusions or auditory hallucinations. Delusions commonly observed in paranoid schizophrenia may include mistrust, suspicion, or the belief that the individual is in danger or being attacked by others. These symptoms can trigger a tendency for the individual to become obsessed with these negative thoughts or beliefs, which in turn can affect their behavior and social interactions.